PARTIAL REGULARITY FOR PARABOLIC SYSTEMS WITH VMO-COEFFICIENTS - Mons, Léon (Communications on Pure and Applied Analysis, 2021)
In this article we establish a partial Holder continuity result for weak solutions of parabolic systems, where the nonlinear vector field A(.) satisfies a standard p-growth condition and a non-degenerate ellipticity condition with respect to the gradient variable, while in the space-time variable z = (x, t) it verifies a VMO-type condition. Thus, no continuity in the space-time variable is assumed. The proof is based on the method of A-caloric approximation, applied on suitably chosen intrinsic cylinders.
CRIS-Team WoS Importer:2021-05-28